A voltage scanning-based MPPT method for PV power systems under complex partial shading conditions - Celikel, Resat; Yilmaz, Musa; Gundogdu, Ahmet (Pergamon-Elsevier Science Ltd, 2022)
Maximum Power Point Tracking (MPPT) algorithms have developed to minimise the effect of the at-mospheric changes. Partial shading conditions (PSCs) are an important cause of MPP changes in photovoltaic systems. In this study, the maximum power point of a PV system was found within a short period in a complex PSC by using voltage scanning. This proposed method can be used in simple and low-level microprocessors. An ever-increasing reference voltage in the proposed method was used to adjust the output voltage of the panels. MP points forming during the voltage increase were recorded and the largest value was used. Thus, a simple algorithm was formed by using the sample-hold blocks. This method was under six PS scenarios on a PV system (2 kW) consisting of eight panels that were formed in a MATLAB/Simulink environment. We then compared voltage scanning method with Cuckoo Search (CS) algorithm (an optimisation method) and presented the findings in detail. The proposed al-gorithm reached maximum power of 99.84% in the third scenario, and 99.9% in the other scenarios. The global MPP capture times in all six scenarios were between 0.078 and 0.262 s. This value is quite good compared to the CS algorithm.(c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Photovoltaic system; Partial shading condition; MPPT; Voltage scanning